An Underwater Wireless Sensor Network with Realistic Radio Frequency Path Loss Model - Ghaith Hattab; Mohamed El-Tarhuni; Moutaz Al-Ali; Tarek Joudeh; Nasser Qaddoumi (International Journal of Distributed Sensor Networks)
We propose an Underwater Wireless Sensor Network (UWSN) for near-shore applications using electromagnetic waves (EM). We also introduce a realistic path loss model for estimating the attenuation encountered by EM waves in underwater environments. The proposed model takes into account the variation of the seawater complex-valued relative permittivity with frequency in contrast to previous work that treats the permittivity as a real-valued constant parameter. Furthermore, the proposed model accounts for the impedance mismatch at the seawater-air boundary, which results in a more realistic estimate of the signal attenuation. Simulation results show the expected signal levels underwater for different scenarios. A prototype implementation to measure the path loss is also presented.